Management of Atrial Fibrillation in Patients Undergoing Percutaneous Coronary Intervention - Mirra, M (University of Salerno, 2014)
Atrial fibrillation (AF) is the most common cardiac arrhythmia, occurring in 1-2% of overall population, involving more than 6 millions of European people. It is associated to a reduced quality of life and an increased morbidity and mortality. The Framingham study showed the link between angina and AF. The same risk factors, such as hypertension, diabetes and obesity promote both AF and coronary artery disease (CAD). About 1/4 of AF patients develop a CAD and, in this setting, about 1/5 undergoes a percutaneous coronary intervention (PCI). In patients with both AF and CAD, the optimal medical strategy is challenging and it is still debated in cardiological community, since patients treated by dual (two antiplatelets drugs ore one antiplatelets drug and an oral anticoagulant drug) or triple therapy (two antiplatelets drugs and an oral anticoagulant drug) are exposed to divergent risk of bleeding or thromboembolic and ischemic complications. Aim of this paper is to focus the attention on the different problems arising from the presence of AF in patients undergoing PCI, such as the risk of stroke, bleeding and stent thrombosis.